“TREASURE HOUSE TO THE WORLD:” A GLOBAL ENVIRONMENTAL HISTORY OF THE PORCUPINE GOLD RUSH, 1909-1929 - Jorgenson, Mica (My University, 2018)
The discovery of gold at Porcupine Lake in 1909 brought a well-practiced era of ecological change to northern Ontario. By the early twentieth century gold rushes followed predictable patterns. Deforestation, soil depletion, water-shed modification, rapid immigration, transient populations, “get-rich-quick” ambitions, conflicts with Indigenous people, major fires, and hasty infrastructure development characterized multiple rushes in Africa, the Americas, and Australasia. In the aftermath of the nineteenth century mining booms, the 1909 Porcupine rush brought global gold mining knowledge and technology to northern Canada. At Porcupine, experiments in industrial extraction matured into a set of efficient methods for large-scale corporate extraction of low-grade gold. Although historians traditionally frame gold rushes as national or regional events, Porcupine shows how borders were permeable to people, objects, and ideas moving between mining zones to shape local environmental history. Porcupine’s gold-bearing landscape became a site of convergent historical forces between 1909 and 1929. The rush brought northern Ontario into an international community of mining frontiers at a moment of development in the province’s northern hinterland. Local conditions (such as climate and geology) worked together with transnational networks to shape the land and its communities. Industrial mining also created problems including fires, droughts, and industrial disease. By 1929, Porcupine had become a major player in the global industrial mining industry. The Porcupine rush set the stage for twenty-first century dominance in international gold economy and laid the groundwork for Canada’s modern relationship with nature.
Keywords: environmental history; natural resources; Canada; Ontario; economic history; transnationalism; geology; mining